1982
DOI: 10.1111/j.1939-165x.1982.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative Disease with Megakaryocytic Predominance in a Dog with Occult Dirofilariasis

Abstract: A 7-year-old male German Shepherd dog with a history of lethargy, weight loss and severe anemia was referred to the University of Florida Veterinary Medical Teaching Hospital for examination. Abnormal laboratory findings included a normocytic and normochromic anemia, thrombocytosis, eosinophilia, basophilia and hyperproteinemia. An increased pulmonary density in the caudal lung lobes was observed on thoracic radiographs. Bone marrow aspiration and core biopsy revealed a hypercellular bone marrow with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Unfortunately, the prognosis for dogs with AMegL and other acute myeloid neoplasms remains extremely grave. 9,17,19,27…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the prognosis for dogs with AMegL and other acute myeloid neoplasms remains extremely grave. 9,17,19,27…”
Section: Discussionmentioning
confidence: 99%
“…In the investigations performed, anemia development in dogs has been mentioned in consequence of decrease in RBC, Hb, and PCV levels (Harvey et al 1982;Atwell and Buoro 1983). Besides, researchers (Harvey et al 1982;Goggin et al 1997) have reported that anemia developing in two different cases have been normocytic normochromic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, researchers (Harvey et al 1982;Goggin et al 1997) have reported that anemia developing in two different cases have been normocytic normochromic anemia. Concurrent with the articles, anemia was identified in four hospitalized dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations